Les points de vue comme strate interprétative - François Nemo (Corela)
The aim of this paper is to show, in relation with Pierre-Yves Raccah’s work, the general existence of a specific interpretative layer, linguistically built to a large extent and which concerns the marking and lexicalization of viewpoints. After recalling the distinction between polysemy and plurisemy (defined as the multi-layered interpretation associated with any use of a word), the argumentative layers at stake (associated with the mechanism of controlled attention and the constraint of scalarity), and the impact of prosody on viewpoints are presented. It is then shown that viewpoints are not limited to argumentative layers and play a crucial role in the determination of the reference of noun phrases. Importantly, is demonstrated on a wide range of examples that the extensional interpretation of such elements is indeed produced by the predicative element (to the point that a negated predicate can be proven to negate something different that what is found in its positive counterpart). Furthermore, in all the examples which are provided, such “semantic restrictions” by the predicate appear to be anchored into specific ways to see the world. This imposes to overcome the alternative between a perspective-free language / world relationship and a world-free language / viewpoint relationship. The world is what is behind the way we access to it, and because languages do not have the capacity to make such viewpoints invisible, they are fully part of the interpretation process, for understanding them is compulsory to have access to what they veil.